NAMPT and BMAL1 Are Independently Involved in the Palmitate-Mediated Induction of Neuroinflammation in Hypothalamic Neurons - Tran, Andy; He, Wenyuan; Jiang, Nan; Chen, Jim T. C.; Belsham, Denise D. (Frontiers in Endocrinology, 2020)
Obesity is a prominent metabolic disease that predisposes individuals to multiple comorbidities, including type 2 diabetes mellitus, cardiovascular diseases, and cancer. Elevated circulating levels of fatty acids contribute to the development of obesity, in part, by targeting the hypothalamus. Palmitate, the most abundant circulating saturated fatty acid, has been demonstrated to dysregulate NAMPT and circadian clock proteins, as well as inducing neuroinflammation. These effects ultimately result in hypothalamic dysregulation of feeding behavior and energy homeostasis. NAMPT is the rate-limiting enzyme of the NAD+ salvage pathway and its expression is under the control of the circadian clock. NAD+ produced from NAMPT can modulate the circadian clock, demonstrating bidirectional interactions between circadian and metabolic pathways. Using NPY/AgRP-expressing mHypoE-46 neurons as well the novel mHypoA-BMAL1-WT/F and mHypoA-BMAL1-KO/F cell lines, we studied whether there were any interactions between NAMPT and the core circadian clock protein BMAL1 in the palmitate-mediated induction of neuroinflammation. We report that palmitate altered Nampt, Bmal1, Per2 and the inflammatory genes Nf-κb, IκBα, Il-6, and Tlr4. Contrary to studies performed with peripheral tissues, the palmitate-mediated induction in Nampt was independent of BMAL1, and basal Nampt levels did not exhibit rhythmic expression. Palmitate-induced downregulation of Bmal1 and Per2 was independent of NAMPT. However, NAMPT and BMAL1 were both involved in the regulation of Nf-κb, IκBα, Il-6, and Tlr4, as NAMPT inhibition resulted in the repression of basal Nf-κb and IκBα and normalized palmitate-mediated increases in Il-6, and Tlr4. On the other hand, BMAL1 deletion repressed basal Nf-κb, but increased basal Il-6. We conclude that NAMPT and BMAL1 do not interact at the transcriptional level in hypothalamic neurons, but are independently involved in the expression of inflammatory genes.